2021
DOI: 10.1161/strokeaha.120.032132
|View full text |Cite
|
Sign up to set email alerts
|

Ten-Year Trend in Age, Sex, and Racial Disparity in tPA (Alteplase) and Thrombectomy Use Following Stroke in the United States

Abstract: Background and Purpose: IV tPA (intravenous thrombolysis with alteplase) and mechanical thrombectomy (MT) utilization increased in acute ischemic stroke hospitalizations in the United States over the last decade. It is uncertain whether this increase occurred equally across all age, sex, and racial groups. Methods: Adult acute ischemic stroke hospitalizations (weighted n=4 442 657) contained in the 2008 to 2017 National Inpatient Sample w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
42
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 22 publications
5
42
1
Order By: Relevance
“…Our findings also reinforce prior literature, as we found that stroke patients from racial or ethnic minority groups in California had lower odds than White patients of receiving reperfusion interventions. 31 , 32 , 33 , 34 This was true for both receipt of alteplase and EVT. Our findings are also consistent with prior work highlighting urban‐rural disparities in access to acute stroke care 35 , 36 that are likely contributing to known rural disparities in stroke patient outcomes.…”
Section: Discussionmentioning
confidence: 86%
“…Our findings also reinforce prior literature, as we found that stroke patients from racial or ethnic minority groups in California had lower odds than White patients of receiving reperfusion interventions. 31 , 32 , 33 , 34 This was true for both receipt of alteplase and EVT. Our findings are also consistent with prior work highlighting urban‐rural disparities in access to acute stroke care 35 , 36 that are likely contributing to known rural disparities in stroke patient outcomes.…”
Section: Discussionmentioning
confidence: 86%
“…(2019) 27 Germany 2016 227687 patients with ischaemic stroke the G-DRG data 14·9% (33916/227687) Otite et al. (2021) 18 US 2008–2017 4442657 patients with ischaemic stroke from National Inpatient Sample 7·0-12·3% across the age spectrum Aguiar de Sousa et al. (2019) 37 44 European countries 2016–2017 1913985 patients with ischaemic stroke from 44 European countries 7·30% Richter et al.…”
Section: Resultsmentioning
confidence: 99%
“…(2017) 26 US 2003–2016 2437975 patients with ischaemic stroke from 2222 hospitals 3·3% in 2016 Otite et al. (2021) 18 US 2008–2017 4442657 patients with ischaemic stroke from National Inpatient Sample 0·7–2·8% across the age spectrum Chen et al. (2019) 6 China 2015 1826332 patients with ischaemic stroke from 1267 tertiary hospitals 0·45% Aguiar de Sousa et al.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations